Investigating the Impact of Universal Free School Meals on the Health and Wellbeing of Primary School Children in Wales: An evaluation using linked data - Locke, Amy; James, Michaela (International Journal of Population Data Science, 2025)
Objectives The introduction of Universal Free School Meals (UFSM) in Wales aims to improve child health and reduce inequalities. Using linked health data we aim to explore UFSM’s impact on healthcare usage, focusing on physical health, mental wellbeing, and social inclusion, while incorporating self-reported wellbeing from the HAPPEN-Wales Cohort and qualitative insights from school staff. Methods Self-reported health and wellbeing trends will be tracked through the HAPPEN (Health and Attainment of Pupils in a Primary Education Network) annual survey. Data linkage through the Secure Anonymised Information Linkage (SAIL) Databank will assess changes in healthcare usage for respiratory conditions, infections, gastrointestinal issues, and behavioural/psychological conditions (e.g., ADHD, depression), to provide a comprehensive understanding of UFSM's potential impact on child health and wellbeing outcomes. These findings will be complemented by qualitative data from teachers, parents, and children, capturing their perceptions of UFSM. Results The availability of health data linkage allows us to track real-life health trends, offering opportunities to compare these findings with self-reported measures and lived experiences. Preliminary qualitative findings reveal mixed perceptions of the provision, including issues around food quality, food choices and the logistical challenges in some settings. Anticipated analyses of linked data is expected to reveal reductions in healthcare usage for respiratory infections, gastrointestinal problems, iron deficiencies, nutritional deficiencies, and mental health outcomes (e.g., reduced GP contacts for ADHD and depression). We hope to provide detail around these linked data findings at the conference. Conclusion The recent roll-out of UFSM in Wales offers a unique opportunity to track both immediate and long-term impacts on children’s health and wellbeing. This research will provide critical insights to inform policy, practice, reduce health inequalities and promote healthier childhoods in Wales.